Scorpion Venom Active Polypeptide May Be a New External Drug of Diabetic Ulcer. (29th October 2017) - Wan, Ting; Li, Luocheng; Zhu, Zhanyong; Liu, Siyang; Zhao, Yueqiang; Yu, Mosheng
Abstract : Background . The epidermal growth factor (EGF) is recognized medicine of therapy in ulcer. However, its efficacy has been challenged. We compared scorpion venom active polypeptide and EGF of therapeutic effects in diabetic ulcer. Methods . The scorpion venom active polypeptide is made into gel. Fourteen diabetic SD rats were randomly divided into scorpion peptide gel group (SPG group) and EGF group. Before treatment, the rat model of diabetic ulcer was created. The levels of IL-1, IL-6, IL-8, and TNF- α in the wound tissue were measured at different time points during the treatment, secretions of wound were collected for bacterial culture, and the wound healing was recorded. Results . Wound healing was faster in SPG group compared to EGF group (3 weeks versus 5 weeks, t -test, p = 0.032 ). The levels of IL-1, IL-6, IL-8, and TNF- α were not statistically different when the wounds were formed but showed significant differences from the 2nd to the 5th week between two groups. The infection rate was higher in the EGF group (42.86% versus 0, Chi-square test, p = 0.025 ). Conclusions . Scorpion venom active polypeptide shortens wound healing with a stronger anti-inflammation and antibacterial effect and may be a new and effective topical drug for the treatment of diabetic ulcers.